Comparative study of female and male soccer players in kicking motion - Sakamoto, K.; Hong, S.; Tabei, Y.; Asai, T. (Procedia Engineering, 2012)
This study compares the male and female soccer players` technical characteristics of ball impact and swing motion before the impact in instep kicks and inside kicks. High-speed video cameras and 3D motion capture were used to examine the characteristics and mechanics of the kicks. During both types of kick, the female players exhibited lower ball velocity, foot velocity immediately before the impact, striking mass, and average ball-to-foot velocity ratio than the male players. The ball-to-foot velocity ratio decreased as the distance of the impact point from the foot's centre of gravity increased. The results of this study suggested that when training female players it is important to instruct them how to impact the ball near the foot's centre of gravity under a variety of conditions. Moreover, the female players exhibited lower inclination of hip and thigh immediately before the impact compared to the male players.